Unifying the detrimental and beneficial effects of social network site use on self-esteem: a systematic literature review. Issue 1 (2nd January 2021) - Krause, Hannes-Vincent; Baum, Katharina; Baumann, Annika; Krasnova, Hanna
ABSTRACT: Previous research offers equivocal results regarding the effect of social networking site use on individuals' self-esteem. We conduct a systematic literature review to examine the existing literature and develop a theoretical framework in order to classify the results. The framework proposes that self-esteem is affected by three distinct processes that incorporate self-evaluative information: social comparison processes, social feedback processing, and self-reflective processes. Due to particularities of the social networking site environment, the accessibility and quality of self-evaluative information is altered, which leads to online-specific effects on users' self-esteem. Results of the reviewed studies suggest that when a social networking site is used to compare oneself with others, it mostly results in decreases in users' self-esteem. On the other hand, receiving positive social feedback from others or using these platforms to reflect on one's own self is mainly associated with benefits for users' self-esteem. Nevertheless, inter-individual differences and the specific activities performed by users on these platforms should be considered when predicting individual effects.